Hippocampal Endosomal, Lysosomal, and Autophagic Dysregulation in Mild Cognitive Impairment: Correlation With Aβ and Tau Pathology. Issue 4 (April 2015) - Perez, Sylvia E.; He, Bin; Nadeem, Muhammad; Wuu, Joanne; Ginsberg, Stephen D.; Ikonomovic, Milos D.; Mufson, Elliott J.
Abstract : Abstract: Endosomal-lysosomal and autophagic dysregulation occurs in the hippocampus in prodromal Alzheimer disease (AD), but its relationship with β-amyloid (Aβ) and tau pathology remains unclear. To investigate this issue, we performed immunoblot analysis of hippocampal homogenates from cases with an antemortem clinical diagnosis of no cognitive impairment, mild cognitive impairment (MCI), and AD. Western blot analysis revealed significant increases in the acid hydrolase cathepsin D and early endosome marker rabaptin5 in the MCI group compared with AD, whereas levels of phosphorylated mammalian target of rapamycin proteins (pmTOR), total mammalian target of rapamycin (mTOR), p62, traf6, and LilrB2 were comparable across clinical groups. Hippocampal Aβ1–40 and Aβ1–42 concentrations and AT8-immunopositive neurofibrillary tangle density were not significantly different across the clinical groups. Greater cathepsin D expression was associated with global cognitive score and episodic memory score but not with mini mental state examination or advanced neuropathology criteria. These results indicate that alterations in hippocampal endosomal-lysosomal proteins in MCI are independent of tau or Aβ pathology.